SIMULATION USING REGRESSION ANALYSIS COMPUTED TOMOGRAPHY SIZES OF MAXILLARY SINUS HEALTHY CITY IN YOUNG PEOPLE AND MEN DEPENDING ON ANTHROPO-SOMATOTYPOLOGICAL INDICATORS - Gunas, I.V.; Shkolnik, E.Ya.; Beliaev Е.V. (World of Medicine and Biology, 2015)
In work, based on the characteristics anthropometric and somatotypological indices using stepwise regression method with inclusion, in practically healthy young men and men of Podillya reliable regression models were built more than for the half of computerized tomographic parameters of maxillary sinuses (MS) with determination coefficient 0.7 and above. Among the predictors computed tomographic parameters of MS most frequently observed cephalometric rate (32.6%), width of distal epiphysis of long bones of the extremities (17.4%) and girth body size (13.0%).